2013
DOI: 10.1099/vir.0.047076-0
|View full text |Cite
|
Sign up to set email alerts
|

West Nile virus NS2A protein facilitates virus-induced apoptosis independently of interferon response

Abstract: The flavivirus NS2A protein is a small, multifunctional protein, involved in replication, virion formation and regulation of the innate immune response. Using the Kunjin strain of West Nile virus (WNV KUN ) we previously demonstrated that a single amino acid change from alanine to proline at position 30 of the NS2A protein (A30P) reduced viral cytopathicity in cells and virulence in mice. To further investigate functions of the NS2A protein we have substituted alanine at position 30 with different amino acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 30 publications
1
30
1
Order By: Relevance
“…Interestingly, no apparent CPE was found in HEK-293 cells transiently transfected with a plasmid harboring a WT DENV NS2A gene driven by the CMV promoter alone. A similar observation was also reported in the overexpression of WNV KUN NS2A, suggesting the other viral proteins in the replication complex are possibly required for NS2A protein to cause CPE of cells (28). Thus, we believe that the DENV NS2A protein may facilitates virus-induced cell death by inducing apoptosis through intrinsic and/or extrinsic apoptotic signaling cascades.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Interestingly, no apparent CPE was found in HEK-293 cells transiently transfected with a plasmid harboring a WT DENV NS2A gene driven by the CMV promoter alone. A similar observation was also reported in the overexpression of WNV KUN NS2A, suggesting the other viral proteins in the replication complex are possibly required for NS2A protein to cause CPE of cells (28). Thus, we believe that the DENV NS2A protein may facilitates virus-induced cell death by inducing apoptosis through intrinsic and/or extrinsic apoptotic signaling cascades.…”
Section: Discussionsupporting
confidence: 55%
“…1B). The CPE-defective phenotypes of the NM5, NM7, NM9, NM17, NM18, and NM19 mutants are similar to that of the A30P WNV KUN NS2A CPE-defective mutant, which failed to induce apoptosis in Vero cells (28). The WNV KUN A30P mutant virus was able to form plaques in BHK21 cells and displayed no apparent reduction in virus yield compared to WT WNV KUN .…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…A second-site reversion mutation at position 149 (from threonine to proline [T149P]) in KUNV NS2A could rescue the defect in virus assembly and secretion and virus production of virus mutants bearing the NS2A-I59N mutation, suggesting a potential interaction between codons 59 and 149. Several lines of evidence have shown that flavivirus NS2A is also involved in the interferon response (15,(23)(24)(25)(26) and virus-induced cytopathic effects (CPEs) (27,28). Recently, the topological study of DENV NS2A suggested that NS2A has eight predicted transmembrane segments (pTMSs; pTMS1 to pTMS8) and five integral transmembrane segments (pTMS3, pTMS4, pTMS6 to pTMS8) that span the lipid bilayer of the endoplasmic reticulum (ER) membrane.…”
mentioning
confidence: 99%
“…Although the precise mechanisms by which wnv induces apoptosis are not completely understood, it has been shown that viral proteins like ns3 and Capsid c induce apoptosis by activating caspases 8 and 3 [41,42]. Also, Balmori et al [43] have suggested a possible role of the protein ns2a in the ifn-independent apoptotic cell death. The authors have shown how a single amino acid (alanine or lysine) might control the cytopathic effect and apoptosis in the absence of ifn-伪/尾 response.…”
Section: Immunopathogenesismentioning
confidence: 99%